Wilhelminism and its legacies : German modernities, imperialism, and the meanings of reform, 1890-1930 : essays for Hartmut Pogge von Strandmann /: German modernities, imperialism, and the meanings of reform, 1890-1930 : essays for Hartmut Pogge von Strandmann. ([2008]) - Unknown
No abstract available